The Mulatto Republic : class, race, and Dominican national identity - Mayes, April J. (University Press of Florida, 2014)
This book examines how the Dominican Republic came to value being white over being black, especially given how many Dominicans are of African descent. Mayes looks at a seminal period of Dominican history, from the War of Restoration to the early decades of Trujillo's rule.